Financial And Non-Financial Information in An Integrated Report: Practice of Selected Polish Listed Companies - Boguslawa BEK-GAIK; Anna SUROWIEC (Communications of International Proceedings, 2021)
Aim / Purpose - The aim of the article is to assess the quality of integrated reporting, how the length and content (financial, non-financial information) of integrated reports have changed in the analyzed years, and to compare the compliance of content elements with the IIRC guidelines on the example of selected Polish companies. Design/methodology/approach – The article consists of three parts. The first presents considerations concerning the concept, essence and scope of financial and non-financial information. The second part discusses the purpose, essence and content elements of an integrated report (IR), as well as an overview of literature research on integrated reporting. In the last part, empirical research was carried out on integrated reports of selected Polish listed companies. The article uses the method of literature studies, case studies, and the authors' own practical experience in the area of integrated reporting. Findings – The results of the research have shown the changes and quality of disclosures in the examined integrated reports. Originality/value/contribution – The research is aimed at presenting a critical interpretative perspective. The results of the study complement the research gap of current literature on integrated reporting disclosures in Polish practice. The research presented in the article contributes to current literature on integrated reporting.
Keywords: integrated reporting; integrated report; non-financial disclosure.